2006
DOI: 10.1038/sj.bjc.6603457
|View full text |Cite|
|
Sign up to set email alerts
|

Ovarian cancer in younger vs older women: a population-based analysis

Abstract: To compare the clinico-pathologic prognostic factors and survival of younger vs older women diagnosed with epithelial ovarian cancer. Demographic, clinico-pathologic, treatment, and surgery information were obtained from patients with ovarian cancer from the Surveillance, Epidemiology, and End Results Program from 1988 to 2001 and analysed using Kaplan -Meier estimates. Of 28 165 patients, 400 were o30 years (very young), 11 601 were 30 -60 (young), and 16 164 were 460 (older) years of age. Of the very young, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
109
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(124 citation statements)
references
References 42 publications
9
109
0
6
Order By: Relevance
“…A majority of these studies were able to adjust for at least age, stage, and histology. Using a significance level of p B 0.05, six of these found that whites had significantly greater survival than African Americans [12,14,15,20,24,29], one found non-whites had greater survival [2], and five found no difference [26,28,30,32,36]. With whites as the referent, the reported HR for death among African Americans ranged from 0.93 to 1.32 [2,29].…”
Section: Survival Outcomesmentioning
confidence: 86%
See 1 more Smart Citation
“…A majority of these studies were able to adjust for at least age, stage, and histology. Using a significance level of p B 0.05, six of these found that whites had significantly greater survival than African Americans [12,14,15,20,24,29], one found non-whites had greater survival [2], and five found no difference [26,28,30,32,36]. With whites as the referent, the reported HR for death among African Americans ranged from 0.93 to 1.32 [2,29].…”
Section: Survival Outcomesmentioning
confidence: 86%
“…Some of the adjusted results had statistical errors; Chan et al (2008) reported HR for categorical variables without the apparent use of dummy variables, for example. Roughly, half of the studies adjusted for all known confounders such as age, disease stage, or treatment status [2,12,20,24,26,28,32,36]. Not adjusting for stage or treatment status in the measurement of survival disparities leads to a biased result likely away from the null value (comparatively poorer survival for African Americans compared with whites).…”
Section: Discussionmentioning
confidence: 96%
“…In univariable analysis, the FIGO stage and histological type showed a strong correlation with a poor PRS. Based on the prior report, the age may be a potent prognostic indicator [18]. In addition, according to the previous study, presence of adjuvant chemotherapy was associated with significantly improved oncologic outcome in patients with early-stage EOC [8].…”
Section: Multivariate Analysesmentioning
confidence: 96%
“…Less than 15% of ovarian cancers are diagnosed in women under age 50, many of which are of nonepithelial histology [9]. • For ovarian cancer patients, increasing age has been considered to be a poor prognostic factor for overall survival [10][11][12][13][14][15]. Age may be a surrogate marker for poor performance status, compounded medical problems, more advanced disease, suboptimal treatment (less radical surgery, less aggressive adjuvant treatment), increased treatmentrelated complications, and challenges in access to medical care.…”
Section: Ovarian Cancer and Agementioning
confidence: 99%